Legal Guarantees for Healthcare Workers During Epidemics and Emergencies - Toshmatova Visolakhon Ikrom kizi (Scientific Trends, 2024)
The article examines the legal guarantees for healthcare workers both in historical periods and in the modern world, with a focus on their protection during epidemics and emergencies. Particular attention is paid to international legal norms, such as the Universal Declaration of Human Rights, ILO Convention No. 155, and WHO International Health Regulations, which form the foundation for protecting healthcare workers. Examples of national regulations in Uzbekistan, the USA, and EU countries are discussed, highlighting major challenges such as resource shortages, legal insecurity, and professional burnout. The conclusion outlines proposals to strengthen legal protections, including the development of an international document regulating healthcare workers' rights during crises.
Keywords: Legal guarantees, healthcare workers, epidemics, emergencies, international law, labour protection, ILO convention, human rights, burnout, personal protective equipment (PPE).